Target Tracking Feature Selection Algorithm Based on Adaboost - Chen Yi (Institute of Advanced Engineering and Science, 2014)
With the development of image processing technology and popularization of computer technology, intelligent machine vision technology has a wide range of application in the medical, military, industrial and other fields. Target tracking feature selection algorithm is one of research focuses in the machine intelligent vision technology. Therefore, to design the target tracking feature selection algorithm with high accuracy and good stability is extremely necessary. This paper presents a target tracking feature selection algorithm based on Adaboost. It includes Adaboost algorithm’s principle and Adaboost algorithm's application in video object tracking. Experimental results show that the proposed algorithm has the characteristics of real-time, accuracy and stability. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3688